Exploring new innovation in e-learning / Jamal Othman - Othman, Jamal (Unit Penulisan Dan Penerbitan JSKM, 2022)
Alhamdulillah, the fourth edition of ebook under SIG of e-Learning@CS has been successfully published. Representing the editorial board, I want to express my appreciation to all authors for their participation in this e-book edition. I wish to express my sincere appreciation to Madam Norazah Umar, the Program Coordinator for the Department of Computer and Mathematical Sciences (JSKM) who has given words of encouragement in making this publication a reality. Starting from 2022, the committee of SIG e-Learning@CS has decided to publish this eBook twice a year. This e-book will be published in April and October each year following the evaluation period of MyATP 2.0 system. The fourth edition of the e-book focuses on innovation in teaching. The authors are encouraged to share experiences and ideas that have been applied and implemented since the Open Distance Learning (ODL) approach was introduced during Movement Controls Orders (MCO). A total of 16 papers have been submitted by JSKM lecturers and varieties of teaching innovations have been elaborated and well explained by the authors